Multi-layer fast-insertion carbon-free anode for aluminum electrolysis of oxygen-aluminum co-production and manufacturing method of multi-layer fast-insertion carbon-free anode
By designing a multi-layer fast insertion carbon-free anode, using the negative expansion characteristics and water atomization method of YMO3 and AB2O4 materials, the problem of insufficient resistance to thermal corrosion and oxygen erosion at high temperatures is solved, and the existing carbon-free anode materials are realized. High temperature and low stress function and high electric efficiency performance reduce production costs.
Patent Information
- Application Number
- CN202310836576.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-10
- Publication Date
- 2025-01-14
AI Technical Summary
The carbon anode used in the existing electrolytic aluminum production leads to high greenhouse gas emissions and environmental pollution, and the existing carbon-free anode materials have insufficient resistance to thermal corrosion and oxygen erosion at high temperatures, which cannot meet high conductivity, high toughness and thermal Seismic requirements.
Design a multi-layer quick insertion carbon-free anode, using metal/ceramic composite material, through the sandwich structure of conductive layer, transition layer and electrolytic layer, use the negative expansion characteristics of YMO3 and AB2O4 materials to reduce high temperature stress, and use the water atomization method and gradient sintering technology to form an anode with high temperature and low stress function.
It realizes the excellent corrosion resistance of ceramic phases at high temperatures, reduces the difference in thermal expansion coefficient between the guide rod and the anode, improves the adaptability of carbon-free anode, and has low-temperature self-heating, high-temperature and high-electrical efficiency functions, reducing labor and manufacturing costs.
Smart Images

Figure CN119307978A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrolytic aluminum, and relates to a carbon-free anode for the electrolytic aluminum industry, and in particular to a multi-layer quick-insert carbon-free anode for oxygen-aluminum co-production aluminum electrolysis and a manufacturing method thereof. Background Art
[0002] At present, the electrolytic aluminum industry has a great impact on the environment and is a high-energy consumption and high-pollution industry. Most industrial production uses carbon anode materials, molten cryolite as solvent, and alumina as solute. After passing through strong direct current, an electrochemical reaction is carried out at about 900°C at the two poles in the electrolytic cell to produce aluminum. In the process, gas emissions such as carbon dioxide, carbon monoxide and perfluorocarbons (CF4 and C2F6) are produced. Carbon dioxide can cause the effect of greenhouses and is the main cause of global warming. The greenhouse effect of CF4 and C2F6 is 6500-10000 times that of carbon dioxide. Carbon monoxide is a toxic gas. When the concentration is high, it will cause poisoning and serious death. The minimum death concentration for human inhalation is 5000ppm (5 minutes).
[0003] In order to protect the environment and human health, it is necessary to remove the carbon element in the electrolytic anode and use a carbon-free anode to reduce the impact on the environment and the harm to humans. At present, the main carbon-free anode materials are ceramic oxides, alloys and metal ceramics. However, all three materials cannot have high resistance to thermal corrosion and oxygen permeation, and at the same time have high conductivity, high toughness and thermal shock resistance. Summary of the invention
[0004] In view of the technical problems existing in the prior art, the present invention combines the advantages of three carbon-free anode materials, designs a new material system, and develops a multi-layer quick-plug anode. The guide rod and the anode are integrally formed. By adding a YMO3 stabilizing phase to the conductive layer, the high-temperature stress between the layers is reduced by utilizing its negative expansion characteristics.
[0005] The present invention is achieved through the following technical solutions.
[0006] The invention discloses a multi-layer quick-insert carbon-free anode for aluminum electrolysis with oxygen-aluminum cogeneration, which is a metal / ceramic composite material with high electrical efficiency and low stress at high temperature. It is composed of a conductive layer core, a transition layer and an electrolytic layer coated in sequence to form a sandwich structure.
[0007] in:
[0008] The conductive layer is composed of a uniform composite of the stable phase perovskite type YMO3, the conductive phase TiX and the bonding phase.
[0009] YMO3: The mass ratio of binder phase: TiX is = (0.05-0.3): (0.05-0.4): 1; wherein Y is the rare earth element yttrium, M is two or more of Co, Cr, Ni, Fe, and Mn, and X is one or more of B, C, and N;
[0010] The transition layer is composed of materials with a mass ratio of AB2O4:binding phase = (0.1-0.4):1; A and B are one or more of Fe, Co, Mn and Ni, and A and B are not repeated;
[0011] The electrolytic layer is a composite of materials with a mass ratio of AB2O4:binding phase = 1:(0.1-0.4); A and B are one or more of Fe, Co, Mn, and Ni, and A and B are not repeated;
[0012] The mass ratio of the conductive layer, the transition layer and the electrolytic layer is (0.5-1):(0.05-0.3):1.
[0013] The bonding phase is an iron-based alloy, and the components by mass percentage are: Ni 8-20%, Co 0-5%, Cr 1-3%, Cu 5-10%, Si 0-1%, B 0-0.5%, Fe balance; the particle size D90=7-12μm, the oxygen content ≤2000ppm; the melting point is between 1100-1200℃.
[0014] Furthermore, the binder phase is prepared by water atomization, with a melting temperature of 1500-1600° C. and an atomization pressure of 50-80 MPa.
[0015] Furthermore, the preparation steps of the YMO3 or AB2O4 powder material are as follows:
[0016] (1) preparing a solution: respectively preparing Y and M salt solutions or A and B salt solutions of a certain molar concentration, mixing them, and continuously stirring them, and adjusting the pH value to 9-11; wherein the salt solution includes nitrate, sulfate, oxalate, acetate or chloride;
[0017] (2) precipitation: pumping sodium hydroxide solution into the mixed solution prepared in step (1) to form a precipitate;
[0018] (3) Filtration: Use centrifugation or funnel to filter and wash out the precipitate;
[0019] (4) Pre-burning: Pre-burning is carried out in air under air conditions using a muffle furnace or a continuous furnace for 1-2 hours;
[0020] Among them, the sintering temperature of YMO3 is 1100-1300℃, and the sintering temperature of AB2O4 is 220-350℃;
[0021] (5) Crushing and screening: The crushing method used is ball milling, air flow milling or mechanical milling, and air flow classification or vibration screen is used to screen out powder with a particle size of D90 = 8-15 μm;
[0022] The present invention also discloses a method for preparing a multi-layer quick-insert carbon-free anode for aluminum electrolysis using oxygen and aluminum cogeneration, comprising the following steps:
[0023] (S1) mixing: mixing powders at a certain mass ratio, the method used comprising: three-dimensional mixing, ball milling mixing, banburying mixing or high-speed stirring mixing;
[0024] Among them, the mass ratio of conductive layer YMO3: binding phase: TiX: forming agent is (0.05-0.3): (0.05-0.4): 1: (0.1-0.2),
[0025] The mass ratio of transition layer AB2O4: binder phase: forming agent is (0.1-0.4):1:(0.1-0.2),
[0026] The mass ratio of electrolytic layer AB2O4: binding phase: forming agent is 1: (0.1~0.4): (0.1-0.2).
[0027] The molding agent includes: one or a mixture of liquid paraffin, PVA, polyethylene, polypropylene, POM, solid paraffin, carnauba wax, microcrystalline wax, stearic acid, and EVA.
[0028] (S2) Granulation: The materials mixed in step S1 are granulated separately, and the methods used include but are not limited to: spray granulation, scraper granulation, extrusion granulation or rotary granulation, and the particle size is -30 mesh.
[0029] (S3) Pressing: Lay the electrolytic layer, transition layer, conductive layer, transition layer and electrolytic layer in sequence, and perform multi-layer pressing. The filling method adopts layered filling, and the pressing pressure is 600-800t.
[0030] (S4) The pressed anode blank is placed in an atmosphere furnace for gradient sintering, firstly air degreasing at room temperature to 600°C, and then filled with inert gas for high temperature roasting at 1000 to 1300°C. The inert gas is one of nitrogen, argon and helium, with a dew point of ≤-45°C and a purity of ≥99.5%.
[0031] Gradient sintering is adopted and multiple insulation platforms are set up.
[0032] Beneficial effects of the present invention:
[0033] The anode prepared by the present invention can reduce the difference in thermal expansion coefficient between the guide rod and the anode while maintaining the excellent corrosion resistance of the ceramic phase, improve the adaptability of the carbon-free anode, and has the functions of low-temperature self-heating and high-temperature high electrical efficiency. It is integrally formed and easy to disassemble and assemble, thus greatly reducing labor and manufacturing costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The model diagram before and after anode machining in the embodiment, a-before machining, b-after machining, 1-conductive layer, 2-transition layer and 3-electrolytic layer;
[0035] Figure 2 This is the SEM morphology of the binder phase powder used in the examples;
[0036] Figure 3 Schematic diagram of the gradient sintering curve used in the embodiment;
[0037] Figure 4 It is the product after multi-layer pressing in the embodiment;
[0038] Figure 5 The anode after sintering and processing in Example 1;
[0039] Figure 6 The anode after sintering and processing in Example 2;
[0040] Figure 7 This is the anode after sintering and processing in Example 3.
[0041] Figure 8 Voltage-time curve during operation of Example 1;
[0042] Fig. 9 Voltage-time curve during operation of Example 2;
[0043] Fig.10 Voltage-time curve during operation of Example 3. DETAILED DESCRIPTION
[0044] The technical solution of the present invention is further described below through specific embodiments in combination with the accompanying drawings.
[0045] Embodiment 1:
[0046] (1) Take 1.5kg of yttrium nitrate, 1.25kg of nickel acetate, and 1.3kg of chromium chloride, dissolve them in 5kg of deionized water, and stir them mechanically in a reactor until they are completely dissolved without obvious precipitation. Take 2.21kg of sodium hydroxide and completely dissolve them in 10kg of deionized water. Pump the sodium hydroxide solution into the reactor at a rate of 0.1L / min, control the solution pH at 10-11 with ammonia water, and stir at a speed of 280rpm; after the reaction is completed, centrifuge and filter, wash and dry; then place the material in a muffle furnace, sinter at 1230℃ for 2h, and then perform air flow crushing and classification to obtain D90=10μm stable phase powder YNi 0.5 Cr 0.5 O3.
[0047] (2) 2.5 kg of nickel acetate and 3.2 kg of ferric chloride were dissolved in 10 kg of deionized water, and a sodium hydroxide solution (3.2 kg of sodium hydroxide and 12 kg of deionized water) was prepared. The sodium hydroxide solution was pumped into the reactor at a speed of 0.1 L / min, and the pH of the solution was controlled at 10-11 with ammonia water, and the stirring speed was 280 rpm; after the reaction was completed, centrifugal filtration was performed and the solution was washed and dried; then the material was placed in a muffle furnace and sintered at 320° C. for 4 h; finally, air flow crushing and classification were performed to obtain ferrite powder NiFe2O4 with a particle size of D90=12 μm;
[0048] (3) Weigh 2.4 kg of pure iron ingot, 0.18 kg of pure copper, 0.09 kg of pure cobalt block, 0.03 kg of pure chromium, 15 g of silica, and 0.25 kg of nickel rod, raise the smelting temperature to 1580°C, and start atomization after 15 minutes, with the atomization water pressure at 70 MPa. After sieving, 1.9 kg of binder phase N10 alloy powder with a particle size of D90 = 12 μm is obtained.
[0049] (4) Take YNi 0.5 Cr 0.5 0.15kg of O3 powder, 0.5kg of binder phase N10 powder, 1.33kg of titanium boride and 0.7kg of 20% polyvinyl alcohol solution were mixed and stirred at high speed for 1 hour, and then granulated with a 30-mesh scraper to obtain conductive layer raw material particles.
[0050] Similarly, prepare the powders of transition layer and electrolytic layer, including: 0.2kg ferrite, 0.85kg N10 alloy powder, 0.127kg 20% polyvinyl alcohol solution in transition layer; 3.4kg ferrite, 0.7kg N10 alloy powder, 300g 20% polyvinyl alcohol solution in electrolytic layer.
[0051] (5) A special press is used for multi-layer pressing. The filling method is layered filling. The electrolytic layer, transition layer, conductive layer, transition layer and electrolytic layer are laid in sequence. The pressing pressure is 600t. After pressing, the anode blank is machined to the required shape. Then the anode blank is placed in an atmosphere furnace for gradient sintering, air degreasing is performed at a low temperature of 250-600℃, and then nitrogen is filled for high-temperature baking at 1260℃ for 2.5h.
[0052] The anode obtained in Example 1 was tested and found to have stable performance. Figure 8 The voltage-time curve shows that the voltage is between 3.1 and 3.2.
[0053] Embodiment 2:
[0054] (1) Take 1.2 kg of yttrium oxide, 1.25 kg of nickel acetate, and 0.8 kg of cobalt sulfate, dissolve them in 4.5 kg of deionized water, and stir them mechanically in a reactor for 1 hour. Take 0.9 kg of sodium hydroxide and completely dissolve it in 5 kg of deionized water. Pump the sodium hydroxide solution into the reactor at a rate of 0.1 L / min, control the solution pH at 10-11 with ammonia water, and stir at a speed of 280 rpm; after the reaction is completed, centrifuge filter and wash and dry; then place the material in a muffle furnace and sinter it at 1260 ° C for 2 hours, then perform air flow crushing and classification to obtain D90 = 13 μm stable phase powder YNi 0.7 Co 0.3 O3.
[0055] (2) 2 kg of nickel acetate, 0.5 kg of cobalt sulfate, and 3.2 kg of ferric chloride were dissolved in 10 kg of deionized water, and a sodium hydroxide solution (3.2 kg of sodium hydroxide and 12 kg of deionized water) was prepared. The sodium hydroxide solution was pumped into the reactor at a speed of 0.1 L / min, and the pH of the solution was controlled at 10-11 with ammonia water, and the stirring speed was 280 rpm; after the reaction was completed, centrifugal filtration was performed, and the mixture was washed and dried; then the mixture was placed in a muffle furnace and sintered at 350° C. for 4 h; finally, air flow crushing and classification were performed to obtain ferrite powder Ni with a particle size of D90=11.5 μm. 0.8 Co 0.2 Fe2O4;
[0056] (3) Weigh 2 kg of pure iron ingot, 0.25 kg of pure copper, 0.15 kg of pure cobalt block, 0.06 kg of pure chromium, 20 g of silica, and 0.45 kg of nickel rod, raise the smelting temperature to 1580°C, and start atomization after 15 minutes, with the atomization water pressure at 75 MPa. After sieving, 1.85 kg of binder phase N10 alloy powder with a particle size of D90 = 12.8 μm is obtained.
[0057] (4) Take YNi 0.7 Co 0.30.3kg O3 powder, 0.48kg binder phase N10 powder, 1.2kg titanium nitride, 0.2kg ws120 liquid paraffin, and 0.3kg acetone were mixed and kneaded for 1h, and then granulated with a 30-mesh scraper to obtain conductive layer raw material particles.
[0058] Similarly, prepare the powders of transition layer and electrolytic layer, including: 0.28kg ferrite, 0.7kg N10 alloy powder, 0.1kg WS120 liquid paraffin, 0.15kg acetone for transition layer; 2.8kg ferrite, 1.12kg N10 alloy powder, 0.4kg WS120 liquid paraffin, 0.35kg acetone for electrolytic layer.
[0059] (5) A special press is used for multi-layer pressing. The filling method is layered filling. The electrolytic layer, transition layer, conductive layer, transition layer and electrolytic layer are laid in sequence. The pressing pressure is 600t. After pressing, the anode blank is machined to the required shape. Then the anode blank is placed in an atmosphere furnace for gradient sintering, air degreasing is performed at a low temperature of 250-600℃, and then nitrogen is filled for high-temperature baking at 1235℃ for 2.5h.
[0060] The anode obtained in Example 2 was tested and found to have stable performance. Fig. 9 The voltage-time curve shows that the voltage is between 3.2-3.3.
[0061] Embodiment 3:
[0062] (1) Take 1.2kg of yttrium oxide, 0.38kg of nickelous oxide, and 0.8kg of cobalt sulfate, dissolve them in 4.5kg of deionized water, and stir them mechanically in a reactor for 1h. Take 0.5kg of sodium hydroxide and completely dissolve it in 3kg of deionized water. Pump the sodium hydroxide solution into the reactor at a rate of 0.1L / min, control the solution pH at 10-11 with ammonia water, and stir at 280rpm; after the reaction is completed, centrifuge and filter, wash and dry; then place the material in a muffle furnace, sinter at 1260℃ for 2h, and then perform air flow crushing and classification to obtain D90=15μm stable phase powder YNi 0.5 Co 0.5 O3.
[0063] (2) 2.4 kg of nickel acetate, 0.1 kg of cobalt sulfate, and 3.2 kg of ferric chloride were dissolved in 10 kg of deionized water, and a sodium hydroxide solution (3.2 kg of sodium hydroxide and 12 kg of deionized water) was prepared. The sodium hydroxide solution was pumped into the reactor at a speed of 0.1 L / min, and the pH of the solution was controlled at 10-11 with ammonia water. The stirring speed was 280 rpm. After the reaction was completed, centrifugal filtration was performed and the mixture was washed and dried. The mixture was then placed in a muffle furnace and sintered at 320° C. for 4 h. Finally, air flow crushing and classification were performed to obtain ferrite powder Ni with a particle size of D90=10.8 μm. 0.9 Co0.1 Fe2O4;
[0064] (3) Weigh 1.8 kg of pure iron ingot, 0.3 kg of pure copper, 0.15 kg of pure cobalt block, 0.1 kg of pure chromium, 20 g of silica, and 0.6 kg of nickel rod, raise the smelting temperature to 1580°C, and start atomization after 15 minutes, with the atomization water pressure at 80 MPa. After sieving, 1.6 kg of binder phase N10 alloy powder with a particle size of D90 = 13.1 μm is obtained.
[0065] (4) Take YNi 0.5 Co 0.5 0.3kg O3 powder, 0.48kg binder phase N10 powder, 1.2kg titanium nitride, 0.2kg ws120 liquid paraffin, and 0.3kg acetone were mixed and kneaded for 1h, and then granulated with a 30-mesh scraper to obtain conductive layer raw material particles.
[0066] Similarly, prepare the powders of transition layer and electrolytic layer, including: 0.25kg ferrite, 0.8kg N10 alloy powder, 0.1kg WS120 liquid paraffin, 0.15kg acetone for transition layer; 3kg ferrite, 0.9kg N10 alloy powder, 0.4kg WS120 liquid paraffin, 0.35kg acetone for electrolytic layer.
[0067] (5) A special press is used for multi-layer pressing. The filling method is layered filling. The electrolytic layer, transition layer, conductive layer, transition layer and electrolytic layer are laid in sequence. The pressing pressure is 600t. After pressing, the anode body is machined to the required shape. Then the anode body is placed in an atmosphere furnace for gradient sintering, air degreasing is performed at a low temperature of 250-600℃, and then nitrogen is filled and calcined at a high temperature of 1250℃ for 2.5h.
[0068] The anode obtained in Example 3 was tested. Fig.10 The voltage-time curve shows that the voltage is between 3.05-3.25, which is slightly lower than the anodes of Examples 1 and 2.
Claims
1. A multi-layer quick-insert carbon-free anode for aluminum electrolysis with oxygen and aluminum cogeneration, which is a metal / ceramic composite material and has high electrical efficiency and low stress at high temperatures, characterized in that: The sandwich structure consists of a conductive layer core, a transition layer and an electrolytic layer wrapped in sequence, wherein: The conductive layer is composed of a stable phase perovskite type YMO3, a conductive phase TiX and a binder phase, wherein Y is a rare earth element yttrium, M is two or more of Co, Cr, Ni, Fe and Mn, and X is one or more of B, C and N; The transition layer is composed of AB2O4 and a bonding phase; A and B are one or more of Fe, Co, Mn and Ni, and A and B are not repeated; The electrolytic layer is composed of AB2O4 and a bonding phase; A and B are one or more of Fe, Co, Mn, and Ni, and A and B are not repeated.
2. The multi-layer quick-insert carbon-free anode for aluminum electrolysis with oxygen and aluminum cogeneration according to claim 1, characterized in that: In the conductive layer, the mass ratio of YMO3:binding phase:TiX is (0.05-0.3):(0.05-0.4):1; In the transition layer, the mass ratio of AB2O4:binding phase is (0.1-0.4):1; In the electrolytic layer, the mass ratio of AB2O4:binding phase is 1:(0.1~0.4); The mass ratio of the conductive layer, the transition layer and the electrolytic layer is (0.5-1):(0.05-0.3):
1.
3. The multi-layer quick-insert carbon-free anode for aluminum electrolysis with oxygen and aluminum cogeneration according to claim 1, characterized in that: The bonding phase is an iron-based alloy, and the components are as follows by mass percentage: Ni 8-20%, Co 0-5%, Cr 1-3%, Cu 5-10%, Si 0-1%, B 0-0.5%, Fe balance; the particle size D90=7-12μm, the oxygen content ≤2000ppm; the melting point is between 1100-1200℃.
4. The multi-layer quick-insert carbon-free anode for aluminum electrolysis with oxygen and aluminum cogeneration as claimed in claim 3, characterized in that: The bonding phase is prepared by water atomization, with a melting temperature of 1500-1600° C. and an atomization pressure of 50-80 MPa.
5. The multi-layer quick-insert carbon-free anode for aluminum electrolysis with oxygen and aluminum cogeneration according to claim 1, characterized in that: The preparation steps of YMO3 are as follows: (1) preparing a solution: respectively preparing Y salt and M salt solutions of a certain molar concentration, mixing them, and continuously stirring, and adjusting the pH value to 9-11; the salt solution includes nitrate, sulfate, oxalate, acetate or chloride; (2) precipitation: pumping sodium hydroxide solution into the mixed solution prepared in (1) to form a precipitate; (3) Filtration: Use centrifugation or funnel to filter and wash out the precipitate; (4) Pre-sintering: Pre-sintering is performed in air for 1-2 hours using a muffle furnace or a continuous furnace, with a sintering temperature of 1100-1300°C; (5) Crushing and screening: The crushing method used is ball milling, air flow crushing or mechanical grinding, and air flow classification or vibration screen is used to screen out powder with a particle size of D90 = 8-15 μm.
6. The multi-layer quick-insert carbon-free anode for aluminum electrolysis with oxygen and aluminum cogeneration as claimed in claim 1, characterized in that: The preparation steps of AB2O4 are as follows: (1) preparing a solution: preparing a salt solution A and a salt solution B of a certain molar concentration, mixing them, and continuously stirring them, and adjusting the pH value to 9-11; the salt solution includes nitrate, sulfate, oxalate, acetate or chloride; (2) precipitation: pumping sodium hydroxide solution into the mixed solution prepared in (1) to form a precipitate; (3) Filtration: Use centrifugation or funnel to filter and wash out the precipitate; (4) Pre-sintering: Pre-sintering is performed in air for 1-2 hours using a muffle furnace or a continuous furnace, with a sintering temperature of 220-350°C; (5) Crushing and screening: The crushing method used is ball milling, air flow crushing or mechanical grinding, and air flow classification or vibration screen is used to screen out powder with a particle size of D90 = 8-15 μm.
7. The method for preparing the multi-layer quick-insert carbon-free anode for aluminum electrolysis with oxygen and aluminum cogeneration according to any one of claims 1 to 6, characterized in that: The steps include: (S1) Mixing: mixing powders according to a certain mass ratio; Among them, the mass ratio of conductive layer YMO3: binding phase: TiX: forming agent is (0.05-0.3): (0.05-0.4): 1: (0.1-0.2), The mass ratio of transition layer AB2O4: binder phase: forming agent is (0.1-0.4):1:(0.1-0.2), The mass ratio of electrolytic layer AB2O4: binder phase: forming agent is 1: (0.1-0.4): (0.1-0.2); (S2) Granulation: The mixed materials are granulated separately to obtain a particle size of -30 mesh; (S3) Pressing: Laying the electrolytic layer, transition layer, conductive layer, transition layer and electrolytic layer in sequence, and performing multi-layer pressing. The filling method adopts layered filling, and the pressing pressure is 600-800t; (S4) The pressed anode blank is placed in an atmosphere furnace for gradient sintering, firstly air degreasing at a low temperature of room temperature to 400°C, and then high-temperature roasting at 1000 to 1300°C is performed by filling with inert gas.
8. The preparation method according to claim 7, characterized in that: In step (S1), the mixing method comprises: One of three-dimensional mixing, ball milling mixing, banburying mixing or high-speed stirring mixing; the molding agent includes: one of liquid paraffin, PVA, polyethylene, polypropylene, POM, solid paraffin, carnauba wax, microcrystalline wax, stearic acid, EVA or a mixture of several of them.
9. The preparation method according to claim 7, characterized in that: In step (S2), the granulation method includes but is not limited to: spray granulation, scraper granulation, extrusion granulation or rotary granulation.
10. The preparation method according to claim 7, characterized in that: In step (S4), the inert gas is one of nitrogen, argon and helium, with a dew point of ≤-45°C and a purity of ≥99.5%.